1H-NMR-guided isolation of enantiomeric coumarin-monoterpenes with anti-inflammatory activity from Gerbera piloselloides. (November 2022) - Zhao, Chen-xu; Gao, Ha; Yu, Meng; Zhao, Jian-ping; He, Bing-xin; Wu, Jiang-ping; Zhang, Hai-xin; Zhang, Tao; Zou, Zhong-mei
Abstract: 1 H-NMR guided fractionation led to the isolation of twenty-two coumarin monoterpenes from the whole plant of Gerbera piloselloides, among which fourteen were undescribed. All coumarin monoterpenes were initially found to be racemates without optical activity. Subsequently, eleven pairs of optically pure enantiomers were successfully separated by chiral phase HPLC. Their structures and absolute configurations were unambiguously determined based on their spectroscopic data, calculated/experimental electronic circular dichroism (ECD) data, and X-ray diffraction analysis. Bioassays in LPS-treated RAW 264.7 cells revealed that the four compounds possessed moderate anti-inflammatory activity. In addition, the correlations between the cotton effect (CE) from δ -lactone at approximately 210–220 nm in CD spectra and γ-C or the ring fused at γ-C of the skeleton were reported for the first time. Graphical abstract: 1 H-NMR guided fractionation led to the isolation of eleven pairs of enantiomeric coumarin-monoterpenes from the whole plant of Gerbera piloselloides . Image 1 Highlights: 1 H-NMR guide isolation of eleven pairs of enantiomeric coumarin monoterpenes. Seven undescribed pairs of enantiomeric coumarin-monoterpenes were separated. The γ -C makes great contribution for the cotton effect of δ -lactone.